Saúde coletiva: promoção de saúde bucal na gravidez - Garbin, Cléa Adas Saliba [UNESP]; Sumida, Doris Hissako [UNESP]; Santos, Renata Reis dos [UNESP]; Chehoud, Keila Aziz [UNESP]; Moimaz, Suzely Adas Saliba [UNESP] (My University, 2011)
Objective: The aim of this study was to analyze the perception and attitudes about oral health of pregnant women recorded on SIS-Prenatal from Bilac city, São Paulo State. Method: the data collection was through interviews with pregnant women using a semi-structured questionnaire. Pregnant women that were not present on attendance with gynecologist and those whose children were born were excluded of sample. Result: Among the  20 interviewed pregnant women, 80% didn’t received any type of information about oral health during pregnancy, 45% of total didn’t know how to maintain baby’s oral health,  85% didn’t know the mean of carie disease. The majority of pregnant women (95%) interested to make part of projects about promotion of oral health. Conclusion: the future mothers showed little knowledge in relation to preventive proceedings in dentistry and about diseases that could involve their and baby’s oral health. It’s necessary to perform programs about oral health, pointing the cares for mother-baby

Objetivo: Esta pesquisa teve como objetivo analisar a percepção e as atitudes sobre saúde bucal das gestantes cadastradas no SIS Pré-Natal do município de Bilac-SP. Metodologia: Para coleta das informações, foram realizadas entrevistas com as gestantes, utilizando-se um questionário semiestruturado. Foram excluídas da pesquisa as gestantes que não compareceram nos dias de entrevista e as parturientes. Resultado: Das 20 gestantes entrevistadas,  80% não receberam nenhum tipo de informação sobre saúde bucal durante a gestação, 60%  não procuraram o cirurgião-dentista durante a gravidez,  45% não sabem como manter a saúde bucal do bebê e 85%  desconhecem o significado da doença cárie. A maioria das mulheres (95%) mostrou-se interessada em participar de projetos de promoção de saúde bucal. Conclusão: As futuras mães apresentaram pouco conhecimento em relação aos procedimentos preventivos em Odontologia e sobre as doenças que podem acometer a sua saúde bucal e a do bebê. É necessária a realização de programas de educação em saúde bucal, voltados aos cuidados do binômio mãe-filho.
Oral health promotion during pregnancy
Keywords: Pregnant woman; Oral health; Health promotion; Gestante; Saúde bucal; Promoção de saúde